Coronary artery disease, its' socio-demographic and behavioral correlates in urban slum population of Bhubaneswar, India - Ansuman Panigrahi; Soham Thakur; Alpana Mishra; Asis Kumar Ray; Basanta Kumar Behera; Smrutiranjan Nayak (Elsevier, 2024)
Background: Coronary artery disease (CAD) causes 15.5 % of all fatalities worldwide and has increased to epidemic proportions. There is dearth of data pertaining to CAD especially among slum inhabitants in India. The present study aimed to assess the prevalence of CAD and its' socio-demographic and behavioral correlates among slum population of Bhubaneswar. Methods: In a community-based cross-sectional study, we selected 625 adults as study participants using a stratified multistage cluster sampling method and gathered relevant information using a structured interview schedule. Standard protocols were followed while measuring anthropometry, blood pressure, electrocardiograms, fasting blood sugar levels, and serum lipid levels. Results: The overall prevalence of definite CAD and probable CAD was 5.1 % and 7.5 % respectively. Multivariable logistic regression analysis revealed that after adjusting for other variables, currently smoking tobacco (aOR: 3.45; CI: 1.68-7.12), moderate intensity activity (aOR: 3.19; 95 % CI: 1.45-6.79), presence of hypertension (aOR: 1.99; 95 % CI: 1.10-3.59), presence of diabetes (aOR: 2.29; 95 % CI: 1.22-4.33), and body mass index ≥25 (aOR: 2.27; 95 % CI: 1.24-4.15) were significantly associated with coronary artery disease among slum population. Individuals with CAD had significantly higher serum total cholesterol, triglyceride, low density lipoprotein levels and lower high density lipoprotein levels than the control group. Conclusion: The prevalence of any CAD in slum areas of Bhubaneswar was high, as were the majority of the associated factors for CAD. Targeted interventions both at individual and community level are needed to address the risk factors of CAD thereby reducing the burden of CAD in this population.